Analisis Pencarian Lokasi Ekspansi Pembukaan Cabang Trust Vape Store Guna Membangun Citra Brand Menggunakan Sistem Pendukung Keputusan Dengan Perbandingan Metode WASPAS dan MAUT - Ardiansah, Ardiansah; Suriati, Suriati; Liza, Rizko (Universitas Islam Negeri Sumatera Utara, 2022)
Vape or also called electric cigarette is very much in demand at this time because apart from a minimal budget and environmentally friendly, this vape itself has several things that make many people switch from tobacco cigarettes to electric cigarettes or vaping. This vape or e-cigarette makes tears Vape stores want to open branches in several places to build a brand image. On the basis of these problems, by selecting the scientific field of decision support systems by adopting the WASPAS and MAUT methods for the selection of the Trust Vape Store branch, this is able to solve the problem with the criteria in accordance with the qualification standards of the Trust Vape Store. The final result of this research is the creation of a decision support system application that adopts the waspas and death method that is able to answer the problems that exist in the turst vape store to make decisions in selecting the location for the expansion of the torch store branch opening in order to build a brand image using a decision support system with the waspas method. and death. Keywords: Trust Vape Store,Decision Support System,Vape